Adapting to Web standards : CSS and Ajax for big sites - Schmitt, Christopher (Voices that matter., 2008)
After learning the language of design, how does one effectively use standards-based technologies to create visually strong Web sites? The full-color Adapting to Web Standards: CSS and Ajax for Big Sites gives developers a peek into the process of the best designers in the world through the work of high profile, real-world Web sites that made them famous. The book focuses on deconstructing these top-tier large-scale sites with particular attention given to deconstructing CSS.